The boundaries of fetal cardiac intervention: Expand or tighten?. Issue 6 (December 2017) - Gellis, Laura; Tworetzky, Wayne
Abstract: Fetal cardiac intervention (FCI) is a relatively new and continually evolving field, and, for select cardiac defects, offers the potential to alter the progression of the disease and improve outcomes. It is a procedure that requires a collaborative effort between maternal–fetal medicine, interventional cardiology and fetal echo/ultrasound specialists, as well as fetal and maternal anesthesiologists, nursing specialists, and social workers. This article reviews the most recently reported data and advances in FCI. Currently, FCI is most frequently performed in fetuses with severe aortic stenosis (AS) with evolving hypoplastic left heart syndrome (eHLHS), established HLHS with intact or highly restrictive atrial septum (IAS), and pulmonary atresia with intact ventricular septum (PA-IVS) with evolving hypoplastic right heart syndrome (eHRHS). The goal of FCI for eHLHS and eHRHS is to promote a postnatal biventricular circulation with, theoretically, the potential for better long-term outcomes. In HLHS with IAS the aim is to improve survival. Contemporary data for FCI demonstrate limited maternal risks and improving technical success. With experience, FCI in severe AS with eHLHS has shown improved rates of biventricular outcome and early survival. Limited data for PA-IVS show promise for improving postnatal biventricular outcomes; however, for HLHS with IAS, FCI has yet to clearly demonstrate improved survival. FCI has an evolving role in the management of congenital heart defects. Ongoing analysis of disease progression, patient selection and postnatal outcomes, in conjuncture with technologic innovations and a multicenter collaborative approach, is essential as the field expands.